(untitled) (Journal on studies and research of academic knowledge, 2015)
This research had as its general objective to promote, through the National University of Itapúa (UND), possibilities of trans-frontier cooperation in the Encarnación Posadas border region. This proposal is based on the idea that the public universities located in the border regions are key players to achieve a regional integration of a higher quality, promoting the development of their region. This qualitative research, based on documentary analysis, organised in three phases. The first one is an exploratory level as it aims at addressing the essential aspects of UNI’s regional dimension. The second one has for a descriptive level: the University’s agenda regional integration is considered on the base of the explored aspects. The third phase consists of the design of proposals for regional integration promotion in the Encarnación Posadas border region. Once the emerging reality had been determined it was concluded that it was necessary to design and to promote from UNI in collaboration with the National University of Misiones (Argentina), a Specialisation Programme on Strategic Management of Regional Integration, with emphasis on public management, built on Skills-based Education and the Methods of Learning with Projects.